Attention to diversity from artificial intelligence - María de los Ángeles Domínguez-González; Carlos Hervás-Gómez; María Dolores Díaz-Noguera; Manuel Reina-Parrado (Foxton Books, 2023)
Artificial intelligence (AI) is influencing various sectors of society, including the educational field. The use of AI can have great potential in education, however, it is necessary to know both its performance and its limitations. The main objective of this study is to analyze the prompts made by teachers in initial training in relation to the topic of specific educational support needs, classifying them according to Bloom's Taxonomy. For this, 63 students from the first year of the Primary Education Degree in the subject Information and Communication Technology applied to Education participated. The results show that the highest frequency of prompts made by students correspond to the highest levels of Bloom's taxonomy (apply and create), which suggests that students are capable of using the knowledge acquired in the subject to create new learning situations with their future students. This confirms that the implementation of this methodology is beneficial for the development of cognitive and pedagogical skills of future teachers.